Dietary Patterns and Their Association with Metabolic Syndrome and Their Components in Middle-Class Adults from Damascus, Syria: A Cross-Sectional Study - Malda Atasi; Ashuin Kammar-García; Rafael Almendra-Pegueros; Addi Rhode Navarro-Cruz (Journal of Nutrition and Metabolism)
Prior to the 2016 crisis in Syria, a study conducted in Aleppo found the prevalence of metabolic syndrome to be 39.6%, which is known to be favoured by age and poor lifestyle (including physical inactivity and the consumption of hypercaloric foods, rich in saturated fats, concentrated carbohydrates, and salt), so the objective of this study was to identify the association of different dietary patterns with metabolic syndrome and their components. A cross-sectional analytical study was carried out in 104 adults aged 40 to 65 years who did not suffer from previous diseases. The sample was chosen from middle-class citizens of the city of Damascus who were contacted by telephone; they were explained about the study, the information that would be collected, and the studies that should be carried out in the clinical analysis laboratory of the Private University of Syria. A nutritional and food study was carried out using previously validated forms containing 62 items in which the food intake of the participants was studied. We apply principal component analysis and factor analysis to detect nutritional components and dietary patterns. Dietary pattern 3 (foods with simple carbohydrates and saturated fat) increased glucose levels, while dietary patterns 1 (high intake of calories, protein, and saturated fat) and 5 (fast food) increased serum triglyceride levels. In addition, pattern 1 (carbonated beverages, grains, chicken, and meat) was associated with elevated LDL cholesterol levels and the presence of the metabolic syndrome. The study findings suggest that the presence of metabolic syndrome and its components are associated with dietary patterns high in calories, protein, simple carbohydrates, and saturated fat.